Cerium Valence State Distribution: Atomic‐Scale Valence State Distribution inside Ultrafine CeO2 Nanocubes and Its Size Dependence (Small 42/2018). Issue 42 (18th October 2018) - Hao, Xiaodong; Yoko, Akira; Chen, Chunlin; Inoue, Kazutoshi; Saito, Mitsuhiro; Seong, Gimyeong; Takami, Seiichi; Adschiri, Tadafumi; Ikuhara, Yuichi
Abstract : In article number1802915, Tadafumi Adschiri, Yuichi Ikuhara, and co‐workers report the atomic‐scale analysis of the distribution of cerium valence states in surfactant‐modified CeO2 nanocubes using scanning transmission electron microscopy and electron energy loss spectroscopy. A nanosized effect induces local lattice expansion, which results in the increasing amount of Ce 3+ cations in the central layer of the ultrafine CeO2 nanocubes.